YURISDIKSI PELAKSANAAN PIDANA TERHADAP UNDANG-UNDANG PERLINDUNGAN ANAK DARI KEJAHATAN TRAFFICKING DI KOTA SAMARINDA - Oni Rosifany (Prodi Ilmu Administrasi Negara, 2015)
The crime trafficking being a mayor transgression of Human Rights and concerning the national and international law. The applied of law either by the Criminal Code (KUHP) or the Children Protection law as a model for the law enforcements for doing the afford of investigating and the enforcement of law executers. In the Children Protection Law No.23 of 2002 in Article 83, it is obviously mentioned that the criminal sanction for the punitive measure would be at least 15 years in jail and fining at most Rp.300.000.000,00 (three hundred million rupiahs) namely for the traffickers who are doing the trafficking crime, selling or kidnapping the children for themselves or Criminal Code (KUHP) as available in the High Court’s Decision of Samarinda “No.545/Pid.B/2004/PN.Smd”.The Governmentand another institution (in this case the National Committee for Children Protection Law) have got a compulsory and responsibility to protect the children which are facing with the law as mentioned in the Article 59 among others said that “..........children those are exploited as an economy and sexsual and trefficking ones...........”